Mutational rectification of certain defects in the aerial podding genotype ’TAP 5’ of groundnut (Arachis hypogaea) - VANISREE, G; PRASAD, M R (The Indian Journal of Agricultural Sciences, 2013)
A study was initiated to rectify early senescence defect of TAP 5 aerial pod-bearing mutant of ’Tatu’ groundnut (Arachis hypogaea L.) through induction of mutations using the chemical mutagens ethyl methane sulphonate(O.3%) and sodium azide (3mM). Seven slow senescent mutants were identified which bred true. Several agronomically desirable mutants such as compact canopy and profusely branched mutants with shorter internodes were also selected, which retained the aerial pod bearing attribute of the parent.